The Role of e-Commerce: A Systematic Literature Review - Qurtubi; Gisya Amanda Yudhistira; Melinska Ayu Febrianti; Ira Promasanti Rachmadewi; Hari Purnomo, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The implementation of digitalization in industrial sector surely gives impact to several sectors, particularly in business. The development of information technology and rapid economic globalization have initiated the role of e-commerce in economic trading activities over the globe. It takes numerous of researches to initiate online new business. Therefore, it is important to reveal the existence of gap among previous researches. Systematic literature review method is applied to analyse the role of e-commerce in trading activity as well to provide the improvement for future researches. As many as 28 e-commerce related literatures are analysed comprehensively and systematically based on protocol review. The result of research confirms the opportunity for future research on e-commerce system that enables the integration on business processes. The supporting variables of e-commerce include business branding, social and economic development, efficient system e-commerce platform, framework application.